Shared decision‐making and providing information among newly diagnosed patients with hematological malignancies and their informal caregivers: Not "one‐size‐fits‐all". Issue 12 (17th April 2017) - Rood, J.A.J.; Nauta, I.H.; Witte, B.I.; Stam, F.; van Zuuren, F.J.; Manenschijn, A.; Huijgens, P.C.; Verdonck‐de Leeuw, I.M.; Zweegman, S.
Abstract: Objective: To optimize personalized medicine for patients with hematological malignancies (HM), we find that knowledge on patient preferences with regard to information provision and shared decision‐making (SDM) is of the utmost importance. The aim of this study was to investigate the SDM preference and the satisfaction with and need for information among newly diagnosed HM patients and their informal caregivers, in relation to sociodemographic and clinical factors, cognitive coping style, and health related quality of life. Methods: Newly diagnosed patients and their caregivers were asked to complete the Hematology Information Needs Questionnaire, the Information Satisfaction Questionnaire, and the Threatening Medical Situations Inventory. Medical records were consulted to retrieve sociodemographic and clinical factors and comorbidity by means of the ACE‐27. Results: Questionnaires were completed by 138 patients and 95 caregivers. Shared decision‐making was preferred by the majority of patients (75%) and caregivers (88%), especially patients treated with curative intent (OR = 2.7, P  = .041), and patients (OR = 1.2, P  < .001) and caregivers (OR = 1.2, P  = .001) with a higher monitoring cognitive coping style (MCCS). Among patients, total need for information was related to MCCS ( P  = .012), and need for specific information was related to MCCS and several clinical factors. Importantly, dissatisfaction with the information they received was reported by a third of the patients and caregivers, especially patients who wanted SDM (χ 2  = 7.3, P  = .007), and patients with a higher MCCS (OR = 0.94, P  = .038). Conclusion: The majority of HM patients want to be involved in SDM, but the received information is not sufficient. Patient‐tailored information is urgently needed, to improve SDM.